Design and analysis of evaluation trials of genetic resources collections: A guide for genebank managers - International Plant Genetic Resources Institute (2000)
This guide is for genebank managers who are considering undertaking evaluation trials on the genetic material in their care. It covers the stages involved in an experimental programme, from the determination of the objectives of each trial to the methods used for the analyses: a broader subject area than that of 'traditional' statistics. The coverage can only give general guidelines, and managers will need to interpret and adapt them for their particular crops. This guide discusses some of the statistical issues that should be borne in mind when conducting an evaluation trial. Managers will also need to consider practical aspects of the way their crops should be grown. A compromise between statistical and practical consideration can be found. This document is intended to stimulate discussion with and among genebank managers on how they could be using their genetic materials to the fullest.